Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) - Wajdi, Badrul; Hizbi, Tsamarul; Ruh Hayati, Baiq Desi (Universitas Hamzanwadi, 2023)
This research aims to produce LKPD problem based learning on the subject of elasticity, to determine the feasibility of LKPD of learning media based on problem based learning on the subject of elasticity, and to determine the effectiveness of LKPD learning media based on problem based learning on the subject of elasticity. The development model used in this research is the 4D model, namely define, design, develop and disseminate. Testing of problem based learning LKPD development products is carried out through validation from material experts, media expertest, subject response questionnaires. Data analysis techniques resulting from the distribution of questionnaires include tabulating data from each validator and calculating the percentage. Based on research results from 3 mateerial experts, it shows that the LKPD is included in the very decent category with a percentge score of menwhile, the assesment resultss from media experts show that the quality of the LKPD is included in the very decent category with a percentage score of percentage. And based on the assessment results of 2 subject teachers, it shows that the qulity of the LKPD is included in the very decent ctegory with score percentage of